Rehabilitation after paediatric acquired brain injury: Longitudinal change in content and effect on recovery. (9th March 2022) - Forsyth, Rob J.; Roberts, Liz; Henderson, Rob; Wales, Lorna
Abstract : Aim: To describe cross‐sectional and longitudinal variation in neurorehabilitation content provided to young people after severe paediatric acquired brain injury (pABI) and to relate this to observed functional recovery. Method: This was an observational study in a cohort of admissions to a residential neurorehabilitation centre. Recovery was described using the Pediatric Evaluation of Disability – Computer Adaptive Testing instrument. Rehabilitation content was measured using the recently described Paediatric Rehabilitation Ingredients Measure (PRISM) and examined using multidimensional scaling. Results: The PRISM reveals wide variation in rehabilitation content between and during admissions primarily reflecting proportions of child active practice, child emotional support, and other management of body structure and function. Rehabilitation content is predicted by pre‐admission recovery, suggesting therapist decisions in designing rehabilitation programmes are shaped by their initial expectations of recovery. However, significant correlations persist between plausibly‐related aspects of delivered therapy and observed post‐admission recovery after adjusting for such effects. Interpretation: The PRISM approach to the analysis of rehabilitation content shows promise in that it demonstrates significant correlations between plausibly‐related aspects of delivered therapy and observed recovery that have been hard to identify with other approaches. However, rigorous, causal analysis will be required to truly understand the contributions of rehabilitation to recovery after pABI. What this paper adds: Rehabilitation content varies widely between, and during, admissions for neurorehabilitation after paediatric acquire brain injury. Strong correlations are seen between plausibly‐related aspects of rehabilitation content and observed recovery, though careful interpretation is necessary. What this paper adds: Rehabilitation content varies widely between, and during, admissions for neurorehabilitation after paediatric acquire brain injury. Strong correlations are seen between plausibly‐related aspects of rehabilitation content and observed recovery, though careful interpretation is necessary. We examine the content of neurorehabilitation provided to young people recovering after severe paediatric acquired brain injury (pABI). Content varies widely between and during admissions and is predicted by pre‐admission recovery suggesting rehabilitation programmes are shaped by therapists' expectations of recovery. However significant correlations persist between plausibly‐related aspects of delivered therapy and observed post‐admission recovery after adjusting for such effects. Rigorous causal analysis will be required to truly understand the contributions of rehabilitation to recovery after pABI This original article is commented on by Whyte on pages 1057–1058 of this issue.